2015
DOI: 10.1371/journal.pone.0125682
|View full text |Cite
|
Sign up to set email alerts
|

A Temperature-Monitoring Vaginal Ring for Measuring Adherence

Abstract: BackgroundProduct adherence is a pivotal issue in the development of effective vaginal microbicides to reduce sexual transmission of HIV. To date, the six Phase III studies of vaginal gel products have relied primarily on self-reporting of adherence. Accurate and reliable methods for monitoring user adherence to microbicide-releasing vaginal rings have yet to be established.MethodsA silicone elastomer vaginal ring prototype containing an embedded, miniature temperature logger has been developed and tested in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 35 publications
(37 reference statements)
1
15
0
Order By: Relevance
“…Boyd et al [68] describes the development of a technology to address the pivotal issue of inaccurate self-reporting of patient adherence during clinical trials. They report a temperature-monitoring microbicide-releasing vaginal ring that uses DST nano-T temperature loggers to monitor user adherence.…”
Section: Introductionmentioning
confidence: 99%
“…Boyd et al [68] describes the development of a technology to address the pivotal issue of inaccurate self-reporting of patient adherence during clinical trials. They report a temperature-monitoring microbicide-releasing vaginal ring that uses DST nano-T temperature loggers to monitor user adherence.…”
Section: Introductionmentioning
confidence: 99%
“…This temperature was selected based on the temporal variation in macaque vaginal temperature described by Boyd et al . [17] and the normal sheep body temperature measured in this study and by others,[22] with a margin for error to prevent false readings of IVR removal. The reference temperature will need to be optimized in clinical trial to accommodate differences between human and sheep basal temperatures.…”
Section: Discussionmentioning
confidence: 83%
“…Until recently, no methods for real-time monitoring of IVR adherence had been reported. Boyd, et al demonstrated proof-of-principle for using IVR temperature as a surrogate measure of adherence [17]. They employed a commercially available temperature logging device inserted in the vaginal cavity to continuously monitor device temperature, and compared it to intravaginal (body) temperature to determine periods of device insertion and removal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One device, Exhale, measures the metabolite via a breathalyzer. Additionally, biometric monitors (e.g., vaginal rings) are also being explored, but thus far only in animal models [61]. No publications of these measures have involved RLS to date.…”
Section: Future Eamsmentioning
confidence: 99%